CT Halo sign: A systematic review. Issue 124 (March 2020) - Ray, Animesh; Mittal, Ankit; Vyas, Surabhi
Highlights: Interpretation of CT Halo sign varies with the immune status of patients. Highly specific for invasive fungal infections in neutropenic patients. Cannot differentiate pulmonary aspergillosis from pulmonary mucormycosis. Abstract: Purpose: The CT Halo sign or Halo sign (HS) refers to ground-glass opacity surrounding a nodule or mass in the lung parenchyma. We conducted a systematic review to find the etiological associations of HS. We also evaluated the diagnostic performances of HS for invasive fungal infections (IFI) in immunosuppressed patients. Method: The systematic review was conducted as per PRISMA guidelines. We searched the PubMed and EMBASE database till June 2018 without any restrictions. Only case reports, case series and original articles published in English language were included. A database created from the electronic searches was compiled and subsequent analysis was done. [PROSPERO registration: CRD42018094739] Results: 168 studies were eligible, which included 51 case reports, 15 prospective studies, 102 retrospective studies. A total of 1977 patients (out of 6371) with HS were identified with age range between <1year-94years. The most common diagnosis in the immunosuppressed, mixed, immunocompetent and not specified groups were IFI (86.9 %, n = 1194), Cryptococcosis (51.6 %, n = 124), Cryptococcosis (40 %, n = 20) and lung neoplasms (81.8 %, n = 36) respectively. 14 studies (11 retrospective, 3 prospective) were included in quantitative analysis. The pooled sensitivity(sn), specificity(sp) and odd's ratio (OR) of HS for diagnosing IFI were 50.4 %, 91 % and 6.61 respectively. Also, HS could not reliably differentiate IPA from mucormycosis in the pooled analysis. Conclusions: HS can be seen in a large number of diverse conditions both in immunosuppressed and immunocompetent population. In immunosuppressed patients HS is specific for IFI but cannot rule it out. Additionally, it cannot reliably distinguish between IPA and mucormycosis.